DAMAGE DETECTION IN COMPOSITE CYLINDRICAL PANEL BASED ON FORCED VIBRATION ANALYSIS - Piotr PAJĄK; Marek BARSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2014)
The current work is devoted to the damage detecting inside the composite cylindrical panels. The applied method is based on the analysis of the natural vibration and corresponding mode shapes. The analysis is performed with use of finite element method. The internal defect is modeled by the reduction of the composite material stiffness and density in arbitrary chosen elements. In the first step the natural frequencies of the intact structure are computed with use of the modal analysis. Next, the corresponding mode shapes are determined (harmonic analysis) for the damage and intact structure. For the each mode shape the curvature in the longitudinal and circumferential direction are determined. In the location of the damage the change of mode shape curvature are quite different in comparison with intact structure. The proposed method of the damage detecting in the investigated here multilayered cylindrical panel are very sensitive. Even single small flaws with relatively low reduction of the material stiffness as well as its position can be effectively detected and localized.